Landing patterns after block in volleyball: Application for ACL injury - Zahradnik, D.; Jandacka, D.; Farana, R.; Uchytil, J.; Hamill, J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of the present study was to describe landing patterns during initial phase (0-30° knee flexion) of "go" landing after block in volleyball. Nineteen elite female volleyball players served as participants in this study. Eight infrared cameras and two force platforms were employed to collect the kinematic and kinetic data. The players used four different landing patterns during initial phase of the "go" landing after block. The players landed with different knee angle positions at initial contact depending on landing pattern. Results of the current study generally suggest that players may protect the ACL during the initial phase of landing by decreasing knee frontal plane angle and moment in direction from valgus to varus position.